ChemInform Abstract: Preparation and Dielectric Properties of Unfilled Tungsten Bronze Ferroelectrics Ba4RETiNb9O30. Issue 51 (17th December 2013) - Hu, Changzheng; Hou, Lianjie; Fang, Liang; Liu, Laijun
Abstract Novel Ba4LnTiNb9O30 compounds with Ln: La, Pr, Nd, Sm, Eu, and Gd are prepared by solid state reaction of stoichiometric mixtures of CaCO3, Ln2O3, TiO2, and Nb2O5 (1300 °C, 8 h, followed by sintering at 1290—1380 °C for 8 h).